Seroprevalence of human cysticercosis and its associated risk factors among humans in areas of Kaduna metropolis, Nigeria - Agnes Uregwu Edia-Asuke; Helen I Inabo; Samson Mukaratirwa; Veronica J Umoh; Clement MZ Whong; Sunday Asuke; Elijah Ekah Ella (Journal of Infection in Developing Countries)
Introduction: Taenia solium cysticercosis is considered an emerging parasitic zoonosis of global importance due to its impact on both agriculture and public health in developing countries. Epidemiological information on human cysticercosis is limited in Nigeria. This study was conducted to determine the seroprevalence of human cysticercosis in areas of Kaduna metropolis, Nigeria, where small-holder pig farming is practiced. Methodology: A cross-sectional survey was conducted in Kaduna South and Chikun Local Government Areas of Kaduna metropolis, which are widely involved in small-holder pig farming and pork consumption. A total of 300 human sera were collected and tested for the presence of IgG antibodies to T. solium using an enzyme-linked immunosorbent assay (ELISA) technique. A structured questionnaire was used to identify risk factors in the population and was administered to the study population. Results: A total of 43 of 300 sera tested positive to IgG antibodies, indicating a cysticercosis prevalence of 14.3%. Method of pork preparation and history of epilepsy were found to be strongly associated with seropositivity. Epileptics in this study were two times more likely to be seropositive than non-epileptics. A large proportion (74.0%) of the population had very poor knowledge of cysticercosis, and knowledge of cysticercosis was strongly associated with method of pork preparation and respondents’ occupations. Conclusions: A high seroprevalence of human cysticercosis was found in Kaduna South and Chikun Local Government Areas. The main risk and behavioral factors contributing to the high prevalence include poor knowledge of cysticercosis and lack of knowledge on proper pork preparation methods.